Pengaruh Reputasi Auditor, Pertumbuhan Perusahaan, Kompensasi Bonus, Kebijakan Deviden, Kepemilikan Manajerial Terhadap Manajemen Laba (Studi Kasus Industri Kimia dan Farmasi yang Terdaftar di BEI Tahun 2018-2020) - Kartika Dwi Rachmawati; Minanari Minanari (Jurnal Akuntansi dan Pajak, 2023)
This research is to determine the influence of auditor reputation, company growth, bonus compensation, dividend policy, managerial ownership on earnings management. The object of this research is a chemical and pharmaceutical industry company listed on the Indonesia Stock Exchange 2018-2020. This research was conducted on 18 chemical and pharmaceutical industry companies in accordance with predetermined criteria. By using a quantitative approach. Because the data analysis used is in the form of multiple linear regression tests. The sample technique used is purposive sampling using EViews software version 10. Based on the results of this research, it shows that simultaneously the variables of auditor reputation, company growth, bonus compensation, dividend policy, and managerial ownership have a joint effect on earnings management. Meanwhile, partially the auditor's reputation and dividend policy affect earnings management. This is evidenced from the results of the partial test (t test) also showed significant values of two independent variables that support the hypothesis. However, the results of this research show that the variables of company growth, bonus compensation, managerial ownership have no effect on earnings management.